SICK BUILDING SYNDROME AND JOB PERFORMANCE IN WOMEN FACTORY WORKERS - Qayyum, Shazia; Tariq, Shahnila; Younas, Faiz (Journal of Postgraduate Medical Institute, 2020)
Objective: To investigate the relationship between sick building syndrome (SBS) and job performance of women factory workers. Methodology: This was a correlational study. A sample of 200 women working in different industrial sectors including pharmaceuticals, hosiery, polyester fiber, and stitching units was recruited with purposive sampling technique,. Indoor Air Quality (IAQ)1 was employed to assess sick building syndrome while Individual Work Performance Questionnaire (IWPQ)2 was used to assess job performance. Results: Results for correlation analyses revealed significant relationship between SBS and job performance while demographic variables including age, family system, working hours as negatively correlated with SBS and job performance. Moreover, SBS was found to be a significant negative predictor of job performance, while age was found to be a significant negative predictor of contextual and adaptive performance domains of job performance. Conclusion: It was concluded that SBS negatively affects the performance level of the factory workers.